2011
DOI: 10.1109/tbme.2011.2107515
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Vesicoureteral Reflux Using Microwave Radiometry—System Characterization With Tissue Phantoms

Abstract: Microwave (MW) radiometry is proposed for passive monitoring of kidney temperature to detect vesicoureteral reflux (VUR) of urine that is externally heated by a MW hyperthermia device and thereafter reflows from the bladder to kidneys during reflux. Here we characterize in tissuemimicking phantoms the performance of a 1.375 GHz radiometry system connected to an electromagnetically (EM) shielded microstrip log spiral antenna optimized for VUR detection. Phantom EM properties are characterized using a coaxial di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 24 publications
(34 reference statements)
1
34
0
Order By: Relevance
“…According to Snow et al (2011), CT images of children (age 2-5 years) show a distance of about 10 mm from the skin interface to the anterior bladder surface and correspondingly 30 mm to the center of the bladder. A representative CT image depicted in figure 2 displays these distances to be 11.7 mm and 34.3 mm, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Snow et al (2011), CT images of children (age 2-5 years) show a distance of about 10 mm from the skin interface to the anterior bladder surface and correspondingly 30 mm to the center of the bladder. A representative CT image depicted in figure 2 displays these distances to be 11.7 mm and 34.3 mm, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…As the target patient group consists of small children, these potential side effects need to be addressed in future work. Nevertheless, in a recent paper by Snow et al (2011), pathological evaluation of three pigs (where the urine was heated to [40][41][42][43][44] o C) showed that heating could be done without tissue damage, mainly due to the low power levels (10-20 W) needed to maintain elevated bladder temperatures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimization parameters included the number and winding of spiral turns, and thickness and dielectric properties of the substrate and matching layer. A 7cm tapered log spiral was determined most appropriate for recording temperature rise in kidney located 3-5cm below the skin [13,14], and a 2.6cm diameter tapered log spiral was found to maximize coupling through the human skull into brain. [15] Fig .…”
Section: Radiometry Systemmentioning
confidence: 99%
“…In fact, current thermometry devices typically measure only intracavitary surrogates of body temperature that do not accurately reflect core temperature of the deep lying organs, especially brain. Each of these surrogate core temperature measurements has inherent problems with probe placement, time delays in reading changing body temperature, and/or are objectionably invasive [9,10].…”
Section: Introduction (Heading 1)mentioning
confidence: 99%